PENINGKATAN KEWIRAUSAHAAN MUDA BERBASIS LIFE SKILL PROGRAM 5.0 DI SANGGAR BIMBINGAN KEPONG MALAYSIA - Aeni, Ida Nur; Widiatami, Anna Kania; Mudrikah, Saringatun; Ristanto, Riska Dami (Universitas Mataram, 2024)
The government has carried out many entrepreneurship improvement programs. However, the program needs to be more comprehensive and felt by all educational institutions, especially non-formal education. One of them is the Sanggal Bimbingan in Kuala Lumpur. Children at the Sanggar Bimbingan Kepong (SB Kepong) need more infrastructure and resources to develop learning and skills. Skills for SB Kepong children are necessary so that they can improve their standard of living. This service activity aims to increase the entrepreneurial spirit needed by SB Kepong children so that they can open their insights about the importance of entrepreneurship from an early age. The service activities were conducted at SB Kepong, Kuala Lumpur, Malaysia. This service activity focuses on three aspects, namely entrepreneurship, finance, and technology. The entrepreneurship improvement program is carried out by equipping literacy and training in making products with a selling value. In addition, the service team strengthens businesses' financial aspects and digitalization to support entrepreneurial skills. The results of this service activity include SB Kepong children increasing their entrepreneurial skills, which can later open up insights and business potential in a sustainable manner. Furthermore, the service participants were able to capture the potential of waste into products that have a high selling value.